In vitro kinetic study of the squalestatin tetraketide synthase dehydratase reveals the stereochemical course of a fungal highly reducing polyketide synthase. Issue 10 (20th January 2017) - Liddle, Emma; Scott, Alan; Han, Li-Chen; Ivison, David; Simpson, Thomas J.; Willis, Christine L.; Cox, Russell J.
Abstract : The substrate selectivity of the isolated dehydratase (DH) domain of a fungal highly-reducing polyketide synthase is closely related to that of mammalian fatty acid synthase. Abstract : Six potential diketide substrates for the squalestatin tetraketide synthase (SQTKS) dehydratase (DH) domain were synthesised as N -acetyl cysteamine thiolesters (SNAC) and tested in kinetic assays as substrates with an isolated DH domain. 3 R -3-hydroxybutyryl SNAC 3 R -16 was turned over by the enzyme, but its enantiomer was not. Of the four 2-methyl substrates only 2 R, 3 R -2-methyl-3-hydroxybutyryl SNAC 2 R, 3 R -8 was a substrate. Combined with stereochemical information from the isolated SQTKS enoyl reductase (ER) domain, our results provide a near complete stereochemical description of the first cycle of beta-modification reactions of a fungal highly reducing polyketide synthase (HR-PKS). The results emphasise the close relationship between fungal HR-PKS and vertebrate fatty acid synthases (vFAS).